Elucidating the specific mechanisms of the gut-brain axis: the short-chain fatty acids-microglia pathway - Qingyu Cao; Mengmeng Shen; Ruoqiu Li; Yan Liu; Zhen Zeng; Jidong Zhou; Dejun Niu; Quancai Zhang; Rongrong Wang; Jingchun Yao; Guimin Zhang (Journal of Neuroinflammation)
Abstract In recent years, the gut microbiota has been increasingly recognized for its influence on various central nervous system diseases mediated by microglia, yet the underlying mechanisms remain unclear. As key metabolites of the gut microbiota, short-chain fatty acids (SCFAs) have emerged as a focal point in understanding microglia-related interactions. In this review, we further refine the connection between the gut microbiota and microglia by introducing the concept of the “SCFAs-microglia” pathway. We summarize current knowledge on this pathway, recent discoveries regarding its role in neurological diseases, and potential pharmacological strategies targeting it. Finally, we outlined the current challenges and limitations in this field of research. We hope this review provides new insights into the role of the gut microbiota in neuroimmune regulation.